Mapping and measuring the phenomenon of precariousness in Cyprus: challenges and implications - Kosmas, Petros C.; Theocharous, Antonis L.; Ioakimoglou, Elias; Giannoulis, Petros; Vatikiotis, Leonidas; Panagopoulou, Maria; Lamprianou, Lamprianos; Andreev, Hristo; Vatikioti, Aggeliki (My University, 2021)
This research study utilises a mixed design model to empirically measure and address the phenomenon of precarious work and precariousness. For the purposes of this study precariousness is perceived as a condition in which people face specific dangers, risk of disease or accident, material deprivation and poverty. Furthermore, as a result of precarious employment, insufficient income and lack of property, these individuals are not able to cope or be exposed to prolonged periods of unemployment and its subsequent social risks and dangers. By analysing data from the EU-SILC (2020) for Cyprus, the characteristics of precarious employees were identified, along with the factors contributing to precariousness. The majority of precarious workers in Cyprus were women, immigrants and young people. Following this, precarity was examined as a condition in which precariousness and economic vulnerability intersect and interact. Precarious workers accounted for 9,5% of all employees in 2019, whereas those in precarity (i.e., precarious and economically vulnerable) amounted for 4,4% of all employees. The present research attempts to contribute to the discussion of class theory by bringing new variables and introducing new empirical approaches to the examination of precarious employment and precariousness. The results of this study are intended to provide stakeholders with an enhanced understanding of the phenomenon which will ultimately lead to new theoretical and policy avenues towards its reduction and elimination.
Keywords: Precarious work; Precariousness; Class theory